Mother tongue - Martinez, Demetria 1960- (New York One World, 1997)
Nineteen-year-old Mary, longing for something meaningful in her life, agrees to help Jose Luis, a refugee from El Salvador who has been smuggled into the United States as part of a sanctuary movement, and immediately falls in love with both the movement and the man.
105221
Keywords: Man-woman relationships -- United States -- Fiction; Mexican American women -- Fiction; Salvadoran Americans -- Fiction; Roman; United States; Fiction; Love stories